2014
DOI: 10.1063/1.4904416
|View full text |Cite
|
Sign up to set email alerts
|

Laser doping for ohmic contacts in n-type Ge

Abstract: We achieved ohmic contacts down to 5 K on standard n-doped Ge samples by creating a strongly doped thin Ge layer between the metallic contacts and the Ge substrate. Thanks to the laser doping technique used, Gas Immersion Laser Doping, we could attain extremely large doping levels above the solubility limit, and thus reduce the metal/doped Ge contact resistance. We tested independently the influence of the doping concentration and doped layer thickness, and showed that the ohmic contact improves when increasin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, there are also studies achieving activated P concentrations above 1 • 10 20 cm −3 for specific RTA conditions [129,130]. In addition, similar activation levels were obtained by a coimplantation of Sb with RTA [131], the application of several implantation-RTA cycles [132], or generally by using LA [133][134][135].…”
Section: Other Group-iv Semiconductorsmentioning
confidence: 68%
“…However, there are also studies achieving activated P concentrations above 1 • 10 20 cm −3 for specific RTA conditions [129,130]. In addition, similar activation levels were obtained by a coimplantation of Sb with RTA [131], the application of several implantation-RTA cycles [132], or generally by using LA [133][134][135].…”
Section: Other Group-iv Semiconductorsmentioning
confidence: 68%
“…GILD [11,12] is performed in a ultra high vacuum reactor (∼10 −9 mbar) which insures a very low impurity level. A puff of the boron precursor gas, pure BCl 3 , is injected using a pulse valve onto the (100) oriented high resistivity n-type silicon surface to induce a pressure of ∼10 −5 mbar, just enough to saturate the chemisorption sites (figure 1(a)).…”
Section: Ultra-doping: Gildmentioning
confidence: 99%
“…For doping levels above 5 × 10 20 cm −3 , the doping value can be difficult to extract due to matrix effects. However, it was shown that using an oxygen primary beam, the variation of the relative ion yield is the same for B and Si, so that the matrix effect can be corrected by the comparison with the silicon signal and using the relative sensibility factor [12]. Moreover, only the secondary ions at high energy (>100 eV) were used for the analysis, as they are less sensitive to the chemical surrounding.…”
Section: Sims Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22] Here we address both of these challenges by developing a new fabrication method for efficient silicon light-emitting diodes using an original doping technique, gas immersion laser doping (GILD), and investigate spin-dependent recombination in silicon LEDs (SiLEDs). The GILD process [23][24][25][26] allows us to reach doping levels well beyond the solubility threshold which, as we describe below, gives rise to efficient emission, while retaining the well-defined planar geometry necessary to align electric and magnetic fields. Using our SiLEDs, we find that when classical MR effects are suppressed, electroluminescence can be substantially enhanced under a magnetic field near room temperature.…”
Section: Introductionmentioning
confidence: 99%